Prospective of extracellular matrix and drug correlations in disease management - Varish Ahmad (Elsevier, 2021)
The extracellular matrix (ECM) comprises of many structural molecules that constitute the extracellular environment. ECM molecules are characterized by specific features like diversity, complexity and signaling, which are also results of improvement or development of disease mediated by some physiological changes. Several drugs have also been used to manage diseases and they have been reported to modulate ECM assembly, including physiological changes, beyond their primary targets and ECM metabolism. This review highlights the alteration of ECM environment for diseases and effect of different classes of drugs like nonsteroidal anti-inflammatory drugs, immune suppressant drug, steroids on ECM or its components. Thus, it is summarized from previously conducted researches that diseases can be managed by targeting specific components of ECM which are involved in the pathophysiology of diseases. Moreover, the drug delivery focused on targeting the ECM components also has the potential for the discovery of targeted and site specific release of drugs. Therefore, ECM or its components could be future targets for the development of new drugs for controlling various disease conditions including neurodegenerative diseases and cancers.